Visualization of the intracellular location and stability of DNA flowers with a label-free fluorescent probe. Issue 27 (15th May 2019) - Wei, Yu; Xu, Xuehui; Shang, Yingxu; Jiang, Qiao; Li, Can; Ding, Baoquan
Abstract : We present a label-free fluorescent strategy to study the intracellular location and stability of RCA-based DNA flower in live cells. Abstract : Rolling circle amplification (RCA) and rolling circle transcription (RCT) can be used to fabricate various structures and organize functional materials for biological applications. The full understanding of the interactions between RCA/RCT-derived structures and live cells is urgently demanded. Here, we present a label-free fluorescent strategy to study the intracellular location and stability of RCA-based DNA flowers in live cells. The DNA flower structures are co-assembled with carbazole-based biscyanine fluorophores, which are DNA detecting molecules and characterized by restriction of intramolecular rotation (RIR) induced strong fluorescent emission. When biscyanine molecules are encapsulated in the DNA flowers via electrostatic attraction, these confined RIR dyes can produce strong luminescent emission. Using this advantage, we use the RIR enhanced technique for direct visualization of the distribution and degradation of DNA flowers in live cellular systems. Our current research could be adapted to other advanced DNA-based materials, providing a new strategy to fabricate fluorescent DNA materials and realize controllable release of payloads.